Analysis of medieval mtDNA from Napole cemetery provides new insights into the early history of Polish state - Tomasz Płoszaj; Krystyna Jędrychowska-Dańska; Alicja Masłowska; Tomasz Kozłowski; Wojciech Chudziak; Jacek Bojarski; Agnieszka Robaszkiewicz; Henryk W. Witas (Taylor & Francis Group, 2017)
Contemporary historical anthropology and classical archaeology are concerned not only with such fundamental issues as the origins of ancient human populations and migration routes, but also with the formation and development of inter-population relations and the mixing of gene pools as a result of inter-breeding between individuals representing different cultural units. The contribution of immigrants to the analysed autochthonous population and their effect on the gene pool of that population has proven difficult to evaluate with classical morphological methods. The burial of one individual in the studied Napole cemetery located in central Poland had the form of a chamber grave, which is typical of Scandinavian culture from that period. However, this fact cannot be interpreted as absolute proof that the individual (in the biological sense) was allochtonous. This gives rise to the question as to who was actually buried in that cemetery. The ancient DNA results indicate that one of the individuals had an mtDNA haplotype typical of Iron Age northern Europe, which suggests that he could have arrived from that area at a later period. This seems to indirectly confirm the claims of many anthropologists that the development of the early medieval Polish state was significantly and directly influenced by the Scandinavians.